Characterizing and simulating the non-stationarity and non-linearity in unconventional oil reservoirs: Bakken application. (March 2015) - Chu, L.; Ye, P.; Harmawan, I.; Du, L.
Highlights: We pointed out the observed abnormal phenomena in unconventional oil reservoirs and offered an explanation of the physics behind them. We pointed out the root reasons for the different well behaviors in an unconventional reservoir. One is the inherent, nm level pore throat and another is the intervened frac works which destroy the geological stationarity. We pointed out that the confined PVT properties could widen the favored operation window, whereas the compaction effect could significantly impair the ultimate reserve of the wells. We proposed a way to incorporate the combined effects of confined PVT and compaction into the simulation model. We presented statistics for the main uncertainty parameters and associated ranges based on more than 120 well RTA results, and we proposed a practical way for modeling and assessing reserves in unconventional reservoirs based on these statistics. Abstract: This paper presents an innovative integrated methodology and working procedure for characterizing and simulating the strong non-linear and non-stationary features caused by changes in confined pressure–volume temperature (PVT) properties over time and the pressure-dependent permeability related to inherent pore-throat size, as well as the intervened multiple porous media created by multi-stage fracture stimulation. The complicated physics behind the observed phenomena are explored. More specifically, this paper demonstrates and discusses the following: (1) a new rate-transient analysis (RTA) procedure to infer the stimulated reservoir volume (SRV) and fracture parameters; (2) the impact of the non-stationary feature, compaction effect, and pore-throat related PVT properties on the flow regime and well performance; (3) how to incorporate the non-stationary and non-linear features into the reservoir model; (4) the integrated procedure for history matching, performance forecast, and reserve assessment; (5) several field examples in the Bakken to illustrate the procedure. The proposed procedure has been successfully applied for the following: (1) constructing the non-stationary and highly non-linear simulation models; (2) facilitating the history matching by addressing permeability reduction and PVT property variations caused by compaction and capillary pressure; (3) and ensuring more reliable performance forecasts and reserve assessments. The study shows that the reduction of the bubblepoint pressure could be several hundred psi in the typical Bakken rock; moreover, such reduction continues following depletion via the compaction effect. The compaction effect could impair the matrix permeability by up to one order of magnitude. The study reveals the following: (1) the confined PVT properties could widen the favored operation window, whereas the compaction effect could significantly impair the ultimate reserve of the wells; (2) the RTA-inferred SRV-related parameters are the key input for capturing the non-stationary features; (3) the impact on reserve could be over 50% without addressing the aforementioned non-stationary and non-linear issues. This paper explores several unique phenomena in unconventional oil reservoirs which have not previously been published. The proposed analysis and assessment procedure greatly enhances the understanding of unconventional assets, and we feel it will improve the accuracy of long-term rate and reserve forecasts.